Effects of dried distillers grains with solubles and extruded expelled soybean meal on growth performance and carcass characteristics of grow-finish pigs - Benz, J.M.; Tokach, Michael D.; Nelssen, Jim L.; DeRouchey, Joel M.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 120 barrows (maternal line PIC 1050) with an initial BW of 105.7 lb were used in an 83-d trial to study the effects of dried distillers grains with solubles (DDGS) and extruded expelled soybean meal (EESM) on growth performance and fat quality. Pigs were blocked by weight and randomly allotted to one of six treatments with two pigs per pen and 10 pens per treatment. Diets were: a corn-soybean meal control diet with no added fat, corn-EESM diet with no added fat, corn-EESM diet with 15% DDGS, corn-soybean meal diet with 15% DDGS, and 1.55% choice white grease (CWG), corn-soybean meal diet with 3.25% CWG, and corn-soybean meal diet with 4.7% CWG. Diets were formulated to have three dietary iodine value (IV) levels (42, 55, and 62) to compare the impact of fat source within dietary IV levels. On d 83, jowl and backfat samples were collected. Pigs fed the control diet, EESM, or 4.7% CWG had increased ADG compared with pigs fed the diet containing EESM with 15% DDGS. Pigs fed the control diet had increased ADFI compared with all other treatment. Pigs fed EESM with 15% DDGS and the diets with 4.7% CWG had improved F/G compared with pigs fed the control and pigs fed DDGS with CWG. Pigs fed high CWG had greater (P<0.05) loin depth compared with pigs fed low CWG. Pigs fed either of the diets with 15% DDGS had increased backfat IV compared with pigs fed diets without DDGS. Pigs fed EESM had increased backfat IV when compared with the control diet or diets with 3.25 or 4.7% CWG. Adding DDGS to the diet or using EESM increased IV of jowl fat. Adding CWG to the control diet also increased IV of jowl fat. Feeding ingredients with higher levels of unsaturated fat, such as EESM and DDGS, had a greater impact on fat IV than CWG even when diets were formulated to similar IV levels.
Keywords: Swine; Added fat; Pork quality; Iodine value